2016
DOI: 10.1139/cjss-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Depth distribution of mineralizable nitrogen pools in contrasting soils in a semi-arid climate

Abstract: A better understanding of the depth distribution of soil mineralizable nitrogen (N) pools is important to improve prediction of net soil N mineralization. However, our understanding of the depth distribution of these N pools under the semi-arid conditions of western Canada is limited. This study examined the depth distribution of soil mineralizable N pools (k S , the rate constant of a nondepleting zero-order stable N pool, and N L , the size of a depleting first-order labile N pool) of six sites in western Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Our results revealed that soil type and soil horizon had a significant interaction effect on soil TN contents (F = 3.55, p < 0.05). These results are similar to those reported by [15] who observed that the depth distribution of mineralizable N pools varied significantly among sites, and they suggested that such distribution needs to be considered in making predictions of net soil N mineralization. Mean TN content was generally higher in surface soils compared to subsurface soils (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that soil type and soil horizon had a significant interaction effect on soil TN contents (F = 3.55, p < 0.05). These results are similar to those reported by [15] who observed that the depth distribution of mineralizable N pools varied significantly among sites, and they suggested that such distribution needs to be considered in making predictions of net soil N mineralization. Mean TN content was generally higher in surface soils compared to subsurface soils (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The relationships among available N and soil properties can be used across a widespread range of soils, agro‐climatic conditions (Nendel et al., 2019), and cropping systems (Clivot et al., 2017). When relationships change with depth, it is possible to estimate the distribution of mineralizable N pools at different soil depths and thus know how N availability changes throughout the soil profile (Dessureault‐Rompré et al., 2010, 2016). In this way, partial treatments and tillering show that at Day 120 of the wheat's growth period, the mineral N increased as a result of the later N application (Day 108).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modeled rates are not a perfect match with the NEON observations, which were collected from soil to 30 cm depth. However, there is a wealth of data to suggest that rates of N mineralization decline substantially with depth (Chen et al., 2019; Darby et al., 2020; Dessureault‐Rompré et al., 2016). Since it is reasonable to assume that surface soils are making a significant contribution to modeled rates, the data–model comparison should prove useful.…”
Section: Methodsmentioning
confidence: 99%